1918
DOI: 10.1001/jama.1918.26020490014010c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Injection of Epinephrin in Soldiers With "Irritable Heart"

Abstract: of the skin. Five per cent, sterile boric acid ointment is a good dressing covered by sterile gauze pad and bandage, or 10 per cent, sodium bicarbonate ointment.The eyes are washed with solution of boric acid and covered, and the lids protected for some time with bland yellow mercuric oxid ointment and fear of further injury dispelled. Later dusting powder of bismuth and zinc oxid, or of zinc stearate will prove satisfactory for abraded skin areas.Dugouts and holes where a person is likely to sit are to be sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1919
1919
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… Hyperadrenergic orthostatic hypotension18 Orthostatic tachycardia syndrome19,20 Postural orthostatic tachycardia syndrome16 Postural tachycardia syndrome16,52 Hyperadrenergic postural hypotension29 Sympathotonic orthostatic hypotension53 Hyperdynamic β‐adrenergic state17 Idiopathic hypovolemia12 Orthostatic tachycardia plus54 Sympathicotonic orthostatic hypotension10 Mitral valve prolapse syndrome55–57 Soldier's heart58 Vasoregulatory asthenia10 Neurocirculatory asthenia10 Irritable heart59 Orthostatic anemia9 Chronic fatigue syndrome60 …”
Section: Diversity Of Autonomic Dysregulationmentioning
confidence: 99%
“… Hyperadrenergic orthostatic hypotension18 Orthostatic tachycardia syndrome19,20 Postural orthostatic tachycardia syndrome16 Postural tachycardia syndrome16,52 Hyperadrenergic postural hypotension29 Sympathotonic orthostatic hypotension53 Hyperdynamic β‐adrenergic state17 Idiopathic hypovolemia12 Orthostatic tachycardia plus54 Sympathicotonic orthostatic hypotension10 Mitral valve prolapse syndrome55–57 Soldier's heart58 Vasoregulatory asthenia10 Neurocirculatory asthenia10 Irritable heart59 Orthostatic anemia9 Chronic fatigue syndrome60 …”
Section: Diversity Of Autonomic Dysregulationmentioning
confidence: 99%
“…If one accepts the hypothesis that some of the patients with the FMV/MVP syndrome were previously considered to have an irritable heart, soldier's heart, or neurocirculatory asthenia, then physicians have attempted to provide an explanation for these symptoms for more than a century [15][16][17]. In all these earlier observations, metabolic abnormalities, autonomic dysfunction, and hyperresponse to adrenergic stimulation were considered as a possible explanation for the symptoms of the FMV/MVP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Fraser and Wilson [17], working in the Heart Section at a military hospital in England during World War I, demonstrated that very small doses of intravenous adrenaline produced a greater heart rate and blood pressure response in soldiers with an ''irritable heart'' compared to control subjects; they concluded that the sympathetic nervous system was unstable in the irritable heart soldiers. Peabody and his colleagues [16] at the United States Army Hospital, New Jersey, studied the effect of intramuscular injections of epinephrine in soldiers with irritable heart and compared the results to a control group; they also demonstrated a hyperresponse to epinephrine and concluded that ''it is distinctly interesting therefore that so large a proportion should be hypersensitive to epinephrine, and one should at least consider carefully whether an unusually excitable sympathetic nervous system may play a part in determining their condition.'' Boudoulas et al [10] demonstrated that symptomatic patients with the FMV/MVP syndrome, mostly females, with high adrenergic tone at rest had hypersensitivity to isoproterenol administration as manifested by dose-related reproduction of symptoms and greater heart rate response compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, physiologic studies conducted on soldiers with neurocirculatory asthenia during World War I showed adrenergic hyperreactivity to the startle response (Peabody, Clough, Sturgis, Wearn, & Tomkins, 1918). Nine decades later, we are ignorant of the genetic and experiential precursors of the neurochemical perturbations eliciting this overreaction, even at a time when the entire human genome is known!…”
Section: Functional Psychocardiac Disordersmentioning
confidence: 99%